2013
DOI: 10.1080/19443994.2012.734720
|View full text |Cite
|
Sign up to set email alerts
|

Application of the solution-diffusion model for the removal of atrazine using a nanofiltration membrane

Abstract: A B S T R A C TThe solution-diffusion model was used to predict the behaviour of four nanofiltration membranes, two were made of polyamide and the other two were made of polypiperazineamide (DL and DK), when used for the removal of atrazine from aqueous solutions. The mass transfer model applied is very simple and its linearization facilitates rapid calculation of the relevant parameters. The two main parameters, permeate concentration and volumetric permeate flux, are obtained from three different coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Overall, the performance of the cross-flow filtration technique using TFC membrane is comparable and in some cases appeared to be better than those reported techniques viz. polyvinylidene fluoride (PVDF) membrane for removal of DDTs (Pang et al 2010), NF 90 for atrazine (Hidalgo et al 2013;Musbah et al 2013), and NF-DK1812 for diuron (Wang et al 2010).…”
Section: Pesticide Removal By Membrane Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the performance of the cross-flow filtration technique using TFC membrane is comparable and in some cases appeared to be better than those reported techniques viz. polyvinylidene fluoride (PVDF) membrane for removal of DDTs (Pang et al 2010), NF 90 for atrazine (Hidalgo et al 2013;Musbah et al 2013), and NF-DK1812 for diuron (Wang et al 2010).…”
Section: Pesticide Removal By Membrane Filtrationmentioning
confidence: 99%
“…High water permeability and rejection of solutes are features that make low-pressure-driven membranes economically viable in water softening applications, attractive for water purification and removal of harmful organic solutes from water (Yangali-Quintanilla et al 2010). Limited studies on removal of some pesticides like herbicides (Wang et al 2010;Riungu et al 2012;Hidalgo et al 2013;Musbah et al 2013;Karimi et al 2016); fungicides (Drazevic et al 2013), and insecticides (Pang et al 2010;Karimi et al 2016) have been reported using RO and NF membranes. The thinfilm composite (TFC) polyamide RO membrane prepared on polysulfone support in our laboratory was evaluated for the removal of only two phenyl urea herbicides (Mehta et al 2015(Mehta et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have been optimized to predict NF membrane performance for compound separation. The behavior and rejection mechanisms of fruit juice phenolic compounds were analyzed based on the quantitative structure–activity relationship model (Hidalgo et al, ; Banerjee & De, ). However, the effect of molecular state on the performance mass transfer process was not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The solution-diffusion models [38] have been used to depict transfer through membranes after experimentally determining the constants of the models. Systems mass balances together with solution-diffusion mass transfer models have been used to simulate the separation process; mainly, this model has been widely used in reverse osmosis membranes, but it has also been applied to nanofiltration membranes [39]. The model equations used in the present work have previously been discussed in other research works [40].…”
Section: Simplified Solution-diffusion Modelmentioning
confidence: 99%